Improvement of liver stiffness measurement, acoustic radiation force impulse measurements, and noninvasive fibrosis markers after direct‐acting antivirals for hepatitis C virus G4 recurrence post living donor liver transplantation: Egyptian cohort. Issue 9 (25th May 2018) - Alem, Shereen Abdel; Said, Mohamed; Anwar, Ismail; Abdellatif, Zeinab; Elbaz, Tamer; Eletreby, Rasha; AbouElKhair, Mahmoud; El‐Serafy, Magdy; Mogawer, Sherif; El‐Amir, Mona; El‐Shazly, Mostafa; Hosny, Adel; et al.
Abstract : Progression of recurrent hepatitis C is accelerated in liver transplant (LT) recipients. Direct‐acting antivirals (DAAs) have recently emerged as a promising therapeutic regimen for the treatment of hepatitis C virus infection. Rates of sustained virological response (SVR) have drastically improved since the introduction of DAAs. The aim is to elucidate the changes in liver stiffness measurement (LSM) by transient elastography (TE) as well as acoustic radiation force impulse (ARFI) elastography and fibrosis scores after DAA treatment in LT recipients with hepatitis C virus recurrence. A single‐center, prospective study including 58 LT recipients with hepatitis C recurrence who received different sofosbuvir‐based treatment regimens. Transient elastography and ARFI elastography values were recorded as well as fibrosis 4 score (FIB‐4) and aspartate aminotransferase‐to‐platelet ratio index were calculated at baseline and SVR at week 24 (SVR24). The outcome was improvement in LSM and at least a 20% decrease in LSM at SVR24 compared with baseline. The sustained virological response was 98.1%. There was improvement of platelet counts, alanine aminotransferase, and aspartate aminotransferase, which in turn caused improvement in fibrosis scores at SVR24. LSM by TE and ARFI elastography decreased from the baseline median value of 6.3 kPa (interquartile range [IQR]; 4.6 to 8.8 kPa) and 1.28 m/s (IQR; 1.07 to 1.53 m/s) to an SVR24 median value of 6.2 kPa (IQR; 4.85 to 8.9 kPa) and 1.12 (IQR; 0.97 to 1.30 m/s), respectively. Logistic regression analysis showed that baseline viral load was the only significant predictor of improvement in LS after DAA therapy at SVR24. Sofosbuvir‐based treatment resulted in an early improvement in parameters of liver fibrosis in post‐LT patients with hepatitis C recurrence.